Tata Kelola Pembangunan Berkelanjutan dalam Upaya Menghadapi Konflik Agraria di Kawasan Transmigrasi Provinsi Lampung - Junarto, Rohmat; Salim, M. Nazir; Mujiburohman, Dian Aries (PT Penjaminan Infrastruktur Indonesia (Persero), 2025)
Indonesia’s transmigration program, despite its scale and strategic intent, has generated persistent structural issues, including agrarian disputes and social tensions. This study investigates the ineffectiveness of sustainable development governance in transmigration areas and proposes evidence-based policy solutions, with a focus on Lampung Province. Employing a mixed-methods approach, the research integrates in-depth interviews, focus group discussions, field observations, and literature review. The study was conducted in four transmigration sites: Rawa Pitu, Mesuji, Way Tuba, and Ngambur. Data were collected from 35 key informants and secondary sources, and analyzed thematically and spatially using ArcMap 10.8.2 software, alongside a descriptive-narrative method. The findings reveal that, by 2023, a total of 6,397 land plots across 24 locations remained uncertified due to overlapping claims. Besides, approximately 40% of issued land certificates did not match the actual physical boundaries. As of 2024, 65% of land disputes have not been resolved, primarily due to institutional fragmentation and overlapping mandates between the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) and the Ministry of Environment and Forestry (KLHK). Social conflicts, such as those observed in Papan Rejo Village, reflect the limitations of top-down policy approaches and the neglect of local communities’ historical land rights. The study recommends structural reforms in integrating land governance systems, accelerating spatially-based land certification, and adopting inclusive and participatory conflict resolution mechanisms.